Rekomendasi Hasil Analisis Pengendalian Biaya Perbaikan Dermaga Apung di Pelabuhan Talang Duku, Jambi - Triyanto, Triyanto; Simanjuntak, Manlian Ronald A; Naibaho, Pio Ranap Tua (Universitas Batanghari Jambi, 2025)
Indonesia's high logistics costs, reaching 23% of its GDP, highlight the urgent need for port efficiency as a key solution. This study aims to analyze the factors contributing to cost overruns in the floating pier repair project at Talang Duku Port, Jambi, and to formulate effective cost control recommendations. The research employed cost control breakdown structure analysis, multiple linear regression using the Least Squares method via EViews 10, and Interpretative Structural Modeling (ISM) to determine improvement priorities. The findings reveal 21 variables affecting cost overruns, with five dominant factors: design errors, financial difficulties, inflation, poor management and supervision, and ineffective communication. Among these, design errors had the most significant impact, with the highest coefficient (0.064471). Based on ISM analysis, the top priority corrective actions include anticipating sudden design changes, financial difficulties, and inflation, followed by improving project management and communication systems. The study concludes that proper design planning and strong coordination among stakeholders are crucial to minimizing cost overruns and enhancing overall port efficiency.